Beispiel Nr: 07
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 4 x -5 y =43\\ -3 x -7 y = 0 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 4 x -5 y =43\\ II \qquad -3 x -7 y = 0 \\ I \qquad 4 x -5 y =43 \qquad / \cdot\left(-3\right)\\ II \qquad -3 x -7 y = 0 \qquad / \cdot\left(-4\right)\\ I \qquad -12 x +15 y =-129\\ II \qquad 12 x +28 y = 0 \\ \text{I + II}\\ I \qquad -12 x +12 x+15 y +28 y =-129 +0\\ 43 y = -129 \qquad /:43 \\ y = \frac{-129}{43} \\ y=-3 \\ \text{y in I}\\ I \qquad 4 x -5\cdot \left(-3\right) =43 \\ 4 x +15 =43 \qquad / -15 \\ 4 x =43 -15 \\ 4 x =28 \qquad / :4 \\ x = \frac{28}{4} \\ x=7 \\ L=\{7/-3\} \end{array} & \begin{array}{l} \\I \qquad 4 x -5 y =43\\ II \qquad -3 x -7 y = 0 \\ I \qquad 4 x -5 y =43 \qquad / \cdot\left(-7\right)\\ II \qquad -3 x -7 y = 0 \qquad / \cdot5\\ I \qquad -28 x +35 y =-301\\ II \qquad -15 x -35 y = 0 \\ \text{I + II}\\ I \qquad -28 x -15 x+35 y -35 y =-301 +0\\ -43 x = -301 \qquad /:\left(-43\right) \\ x = \frac{-301}{-43} \\ x=7 \\ \text{x in I}\\ I \qquad 4 \cdot 7 -5y =43 \\ -5 y +28 =43 \qquad / -28 \\ -5 y =43 -28 \\ -5 y =15 \qquad / :\left(-5\right) \\ y = \frac{15}{-5} \\ y=-3 \\ L=\{7/-3\} \end{array} \end{array} $